User Interface Design for Discrepancy-Simple Additive Weighting Evaluation Instrument - Sugiarta, I Made; Sugandini, Wayan; Andayani, Made Susi Lissia; Suyas, P. Wayan Arta (Journal of Multimedia Trend and Technology, 2025)
In an effort to make it easier for users to understand how DSS-based instruments function without having to run the actual application, a user interface design is required. The purpose of this study was to show the quality of the user interface design of the Discrepancy-SAW evaluation instrument. The research approach used the R&D development model, which focuses on three stages of development. The three stages were design creation, initial design trial, and revision of the initial design trial. The subjects involved in the initial trial of the user interface design were 40 respondents. The trial tool was a questionnaire consisting of 10 questions related to the user interface design. Analysis of the trial data was carried out by comparing the percentage of user interface design quality with quality standards that refer to the eleven-scale categorization. The results of this study show the quality of the user interface design of the Discrepancy-SAW evaluation instrument in the good quality category by a quality percentage of 83.38%. The impact of the results of this study is that stakeholders in the field of education gain knowledge about the existence of the user interface design of the Discrepancy-SAW evaluation instrument. It is appropriate for use in determining the dominant factors that trigger inequality in the lecture process in the research methodology course.